A Critical and Comparative Analysis of Internalization and Internationalization Theories - Ugalde Binda, Nadia (2008)
Most of scientific literature in businesses administration magazines deal around the subjects of internalization (or transaction costs theory, TCE) and internationalization. Some authors support and others criticize their statements, but few have tried to analyze, to compare and if it is possible to integrate these two important theories. This work focuses in a critical analysis of scientific contributions around these subjects and compares its basic assumptions. Its primary target is to find points of similarity and differences, as well as to provide managers a diversity of appreciations that allow them to adapt the theories to the reality of their surroundings.